HUBUNGAN AKTIVITAS ENZIM DAN KONSENTRASI SUBSTRAT PADA POLA DETEKSI SECARA HPLC HASIL TRANSGLIKOSILASI PINOCEMBRIN OLEH ENZIM SELULASE Trichoderma asperellum LBKURCC1 - Fifira Safitri; Titania Tjandrawati Nugroho; Hilwan Yuda Teruna (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
"> Enzymatic transglycosylation of pinocembrin was successfully carried out by cellulase from Trichoderma asperellum LBKURCC1. However, the reproducibility of the reaction is low, making detection by reverse phase HPLC (High Performance Liquid Chromatography) difficult when the enzyme activity decreases. It is believed that the initial flavonoid concentration used in the transglycosylation reaction influences the detection pattern of transglycosylation product by HPLC, when the enzyme activity is low. In this research, transglycosylation of pinocembrin was done by a concentrated extract of T. asperellum LBKURCC1 cellulase and using CMC (Carboxymethyl Cellulose) as glycosyl donor. The reaction was carried out for 30 hours at 40oC and 170 rpm shaking. Results of HPLC analysis showed that cellulase with activity of (4.3±0.2) U/mL could only obtain 1.7% conversion of pinocembrin to its glycosylated product when the substrate concentration was 6 mg/mL. At these conditions, a barely detectable HPLC peak was observed at retention time of 8.4 minutes. This peak increased noticeably when the initial concentration of pinocembrin was decreased to 0.6 mg/mL. Percent conversion of pinocembrin to its transglycosylation product was 4.3% when the initial substrate concentration was 0.6 mg/mL and the enzyme activity was (4.3±0.2) U/mL.